Investigation of Leaf Gas Exchange Parameters of Several Chestnut Population Seedlings at the End of the Growing Season - Uğur Cantürk; Hatice Çobanoğlu; Fadime Beyazyüz; İsmail Koç (Turkish Journal of Agriculture: Food Science and Technology, 2023)
Changes in temperature and precipitation due to global climate change negatively affect plant species' growth, development, and adaptation to new places. However, genetic structure is the most critical criterion for determining a species's potential to adapt to changing environmental conditions. Monitoring gas exchange parameters in plants is the simplest way to monitor physiological changes in plants under changing environmental factors. Among species, the Anatolian chestnut (Castanea sativa) is native and economically important tree species (fruit and wood production). It is naturally distributed from the north side of Turkey, Marmara, and Western Anatolia. However, the Anatolian chestnut is one of the most affected tree species by global climate change. In this study, numerous Anatolian chestnut populations (3 years old) were used to determine leaf gas exchange parameters at the end of the growing season in Düzce. Stomatal conductance (gs), transpiration rate (E), net photosynthetic rate (Anet), and other parameters were measured. As a result, the leaf gas exchange parameters of chestnut populations changed significantly based on the populations. Marigoule population seedlings had 2-fold Anet values compared to the Ibradı population. Regarding gs, the differences between populations (Erfelek and Ibradı) changed approximately 2.5 folds and the differences (Erfelek and Ibradı) increased more than 3 folds in terms of E values. It can be said that Marigoule and Erfelek populations can adapt more to Düzce climate conditions than other populations. In contrast, Ibradi population seedlings have a low adaptation mechanism in terms of gas exchange traits.